PENINGKATAN KAPASITAS MASYARAKAT DALAM PENGENDALIAN PENYAKIT MENULAR SEBAGAI STRATEGI ADAPTASI PERUBAHAN IKLIM SEKTOR KESEHATAN DI DESA ANTUTAN, KABUPATEN BULUNGAN - Sugiyatmi, Tri Astuti; Kello, Jusfin Asri Patoding; Yanti, Arisda; Ramadhani, Eva; Fatimah, Siti; Hidayatullah, Hidayatullah; Abdullah, Abdullah; Rafiq, M. (Gapenas Publisher, 2024)
The health sector is part of the impact of climate change both directly and indirectly. Climate change affects rainfall and temperature changes, causing disease-transmitting vectors such as mosquitoes to breed more easily. Moreover, it is supported by environmental factors and bad behavior in implementing clean and healthy living. Therefore, in addition to mitigation, efforts to adapt to climate change are important in anticipating the impact. The activity aims to provide supplies to increase community capacity, especially in terms of environmental health and clean and healthy living behavior (PHBS), as an effort as a climate change adaptation strategy. The method was health education with lectures, discussions, and a question-and-answer approach. In addition, a pre-test was previously carried out to fill in open questions related to the topics. All community leaders in Antutan village followed this activity. The activity was implemented on July 17, 2024, in Antutan Village, Tanjung Palas District, Bulungan Regency, North Kalimantan Province. This activity was successful, marked by the enthusiasm of the participants during the presentation as well as the many questions that came in during the question-and-answer session and discussion. Recommendations: The implementation of the Climate Village Program (PROKLIM) activities in Antutan Village for climate change adaptation is very important. Community capacity-building activities in terms of controlling communicable diseases should be made an annual routine agenda. The program should be developed in other community groups